2020
DOI: 10.3389/fpsyg.2020.01684
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of the COVID-19 Outbreak on Health Professionals: A Cross-Sectional Study

Abstract: Background: The COVID-19 pandemic had a massive impact on health care systems, increasing the risks of psychological distress in health professionals. This study aims at assessing the prevalence of burnout and psychopathological conditions in health professionals working in a health institution in the Northern Italy, and to identify socio-demographic, work-related and psychological predictors of burnout. Methods: Health professionals working in the hospitals of the Istituto A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

79
401
11
39

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(582 citation statements)
references
References 49 publications
79
401
11
39
Order By: Relevance
“…Previous studies conducted among HCW in Europe and other parts of the world amid the COVID-19 pandemic revealed that the female and single HCW had more frequently reported anxiety and depression symptoms [8,18], which was similar to our study ndings. A review also has shown that the prevalence of anxiety and depression among Asian female and single HCW during the COVID-19 pandemic was higher than their counterparts [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies conducted among HCW in Europe and other parts of the world amid the COVID-19 pandemic revealed that the female and single HCW had more frequently reported anxiety and depression symptoms [8,18], which was similar to our study ndings. A review also has shown that the prevalence of anxiety and depression among Asian female and single HCW during the COVID-19 pandemic was higher than their counterparts [19].…”
Section: Discussionsupporting
confidence: 92%
“…The total score ranges from 0 to 27. The total score suggests different levels of depressive symptoms: minimal/no depression (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19)(20)(21), and very severe (22)(23)(24)(25)(26)(27). However, in this study, cut-off point ≥ 10 was used to classify participants as having depressive symptoms [14,15].…”
Section: Depression Symptomsmentioning
confidence: 99%
“…In overall, the data showed a slightly lower rate of perceived depression and distress symptoms among HCWs in Vietnam when compared to several reports in China, Italy, or the US. 8,[33][34][35] The difference reflected the fact that Vietnam had a low number of COVID-19 active cases and the majority were in mild condition in the first wave from January to March 2020. In a setting of limited health resources such as Vietnam, flattening the curve of active cases through high-level and aggressive prevention measures could be the most appropriative approach to reduce the burden for the healthcare system, as well as minimize the work pressure and the overwhelmed situation among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that GPs have a high risk of developing burnout syndrome. Recent studies examined the prevalence of burnout during the COVID-19 emergency in health professionals working in Northern Italy ( Giusti et al, 2020 ), showing high levels of burnout especially in Emotional Exhaustion and reduced Personal Accomplishment. These burnout findings were significantly higher than those detected in other Italian samples before the COVID-19 outbreak, especially for Emotional Exhaustion ( Barello et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%